Respuesta :
Answer:
D. (-1, -3)
Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}y=x^2-4&(1)\\y=-2x-5&(2)\end{array}\right\\\\\text{Put (1) to (2):}\\\\x^2-4=-2x-5\qquad\text{add}\ 2x\ \text{and 5 to both sides}\\\\x^2+2x+1=0\\\\x^2+x+x+1=0\\\\x(x+1)+1(x+1)=0\\\\(x+1)(x+1)=0\\\\(x+1)^2=0\iff x+1=0\qquad\text{subtract 1 from both sides}\\\\x=-1\\\\\text{put the value of}\ x\ \text{to}\ (2):\\\\y=-2(-1)-5\\\\y=2-5\\\\y=-3[/tex]
Answer: Hello there!
The system of equation given is:
y = x^2-4
y = -2x-5
And we want to solve this system:
the first step we can do is replace y in the first equation by the given in the second equation:
y = x^2-4 = -2x - 5
now we can solve it for x:
x^2-4 +2x + 5 = 0
x^2 +2x + 1 = 0
and now we can use the cuadratic equation forumla:
this is, if we have a function of the form:
ax^2 + bx + c = 0
the solutions are:
[tex]x = \frac{-b +/- \sqrt{b^2 -4ac} }{2a}[/tex]
in our equation we have a=1, b = 2 and c= 1
we replace it in the formula given, and we obtain:
[tex]x = \frac{-2 +/- \sqrt{2^2 -4*(1)} }{2} = \frac{-2 +/- \sqrt{4 - 4} }{2} = -2/2 = -1[/tex]
Now we got the value of x, and we could replace it in one of the equations and get the value of y:
y = -2x-5
y = -2*(-1) - 5 = 2 -5 = -3
then the pair is (-1, -3)
and the correct option is D.